1998
DOI: 10.1046/j.1365-2419.1998.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐oceanic characterization of zooplankton community size structure using an optical plankton counter

Abstract: The Atlantic Meridional Transect (AMT), sampling between 50°N and 50°S, is a trans‐oceanic research programme to characterize plankton community structure, productivity and bio‐optical properties of the upper ocean in relation to ocean provinces and meso‐scale features. As part of a suite of continuous measurements, an optical plankton counter (OPC) has been used on the AMT to characterize the surface distribution of zooplankton based on their abundance and community size structure. Results from the OPC were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 17 publications
5
17
0
Order By: Relevance
“…The results of continuous measurements of zooplankton abundance and biomass by optical plankton counters in a range from 0.25 to 8.0 mm have indicated that minimal values are typical for the oligotrophic South Atlantic Subtropical Gyre and oligotrophic Canary Basin along a transect from 49°N to 46°S (Gallienne & Robins 1998). Values were 20 times higher in the equatorial region and 10 times higher in the waters near the West African upwelling.…”
Section: Introductionmentioning
confidence: 97%
“…The results of continuous measurements of zooplankton abundance and biomass by optical plankton counters in a range from 0.25 to 8.0 mm have indicated that minimal values are typical for the oligotrophic South Atlantic Subtropical Gyre and oligotrophic Canary Basin along a transect from 49°N to 46°S (Gallienne & Robins 1998). Values were 20 times higher in the equatorial region and 10 times higher in the waters near the West African upwelling.…”
Section: Introductionmentioning
confidence: 97%
“…Such discrepancies are most likely explained by the OPC sensing non-zooplankton particles, e.g., detritus, which can be more numerous than zooplankton (Herman 1992;Heath et al 1999;Zhang et al 2000). It should, nevertheless, be noted that some previous studies have found good agreement between OPC counts and net abundance (Herman 1992;Gallienne and Robins 1998). In our study, the zooplankton assemblage was strongly dominated by a single species, Calanus finmarchicus, making a comparison between the OPC and net data relatively straightforward.…”
Section: Discussionmentioning
confidence: 45%
“…Raymont, 1983). A ¢ve year survey of the Atlantic Ocean along the Atlantic Meridional Transect (AMT; Robins & Aiken, 1996;Aiken & Bale, 2000) sampled the corresponding western part of the South Atlantic, between 4 and 208S, in April/ May of ¢ve consecutive years (Gallienne & Robins, 1998). The average surface mixed layer biomass for the AMT series was 39 mg m À3 .…”
Section: Discussionmentioning
confidence: 99%
“…The OPC produces a reliable and robust estimate of mesozooplankton numbers and size, in the size range 250 mm^16 mm equivalent spherical diameter (ESD), yielding a size distribution which can be converted into biomass (Gallienne & Robins, 1998;. Mesozooplankton biomass (mg m À3 ) data were derived from OPC biovolume (ml m À3 ), assuming a speci¢c gravity for mesozooplankton of 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation